Korelasi Makna Tarian Bonet Masyarakat Dawan Dengan Konsep Relasi Martin Buber (Sebuah Study Komparasi dengan Pendekatan Filosofis) - Banusu, Yeremias (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
The focus of this paper is the correlation between the meaning of Bonet dance in Dawan society with the concept of relations with Martin Buber. The Bonet dance for the Dawan community (TTU Regency, NTT Province) is a dance that expresses harmonious unity and unity marked by a dance around, circling while holding hands, whereas relations acording to Martin Buber are harmonious and mutual relations between humans and humans. There is a correlation between the bonet dance with the concept of Martin Buber relations. This paper is a comparative study with a philosophical approach conducted by the author to find the correlation between the two variables above.